FLUORIDES AND ORAL HEALTH - Boitsaniuk, S. I.; Levkiv, M. O. (International Journal of Medicine and Medical Research, 2023)
Background. The importance of fluorides in caries prevention is discussed in the article and practical recommendations for the use of fluoride containing products are presented. Objectives. The primary objective of this systematic review is to assess the evidence on the comparative effectiveness of topical fluoride therapy (TFT) in the form of toothpastes, mouth rinses, gels and varnishes in prevention of dental caries in children and adolescents. Methods. A systematic electronic literature search was conducted in the PubMed and Web of Science databases using search terms. Current reports in the literature concerning means and methods of use of fluoride-containing medications are considered. Results. A large number of scientific studies, reviews based on them and meta-analyses conclude that the central element of caries prevention, on which the decrease in caries prevalence and caries experience is based, is the regular topical use of fluoride medications for oral cavity. Conclusions. Topical use of fluorides is a key element in successful caries prevention.